Knowledge Level Relationship Management Efforts Mother And Anxiety In Dealing With Menopause In Genuksari Urban District of Semarang Genuk - Fitriani Nur Damayanti (Jurnal LINK, 2013)
Maternal anxiety menopause often occurs with the invisibility of a sense of tension, confusion and fear in the face of physical and psychological changes in dealing with menopause. This study aims to determine the level of knowledge and effort of mothers with maternal anxiety level and know the relationship between the level of knowledge and effort of mothers with maternal anxiety levels in dealing with menopause. This study uses quantitative research using survey research methods. And the approach of using cross sectional study with proportional sampling random sampling of the many subjects in each subgroup or strata must be known in advance comparison. Then determined the percentage of the overall size of the sample population. Sample is 102 responden. The instrument was a questionnaire.